Three Essays on the Effectiveness of Foreign Aid - (:unkn) unknown (My University, 2021)
Throughout three essays, this dissertation investigates three important aspects of the effectiveness of foreign aid: whether and how foreign aid is effective. Chapter 1 explains the background of the study on foreign aid. This introduction chapter also summarizes my arguments and the empirical strategies of each essay. Chapter 2 analyzes when foreign aid helps the recipient countries’ economic growth. In specific, this chapter argues that the political leaders’ survival strategy determines how to spend the aid, and it makes the difference in the aid effectiveness to achieve economic growth. Using a panel dataset for the 82 aid recipient countries between 1960 and 2010, this study finds that foreign aid is more likely to lead to economic growth in the case of a large winning coalition. In Chapter 3, I examine how foreign aid reduces political violence in recipient countries. Based on the findings of Chapter 2, I further argue that aid recipients experience less political violence due to its contribution to economic growth. Utilizing a moderated mediation model, I find that the recipient country achieves positive economic growth in a large winning coalition and consequently experiences fewer civil wars and domestic terrorist attacks. Chapter 4 investigates the effectiveness of foreign aid from the perspective of the donor country. In particular, I argue that foreign aid leads to more export of donor country to the recipient because implementing aid serves as building and enhancing the relationship between donors and recipients. Using Korean bilateral aid and export data to recipient countries between 1965 and 2015, this chapter shows that bilateral aid increases the donor’s export toward recipient countries. The effect becomes more prominent in the long term. Chapter 5 concludes. This concluding chapter emphasizes the main arguments and findings and draws aid policy recommendations.
Keywords: Economic Growth; Export; Foreign Aid; GMM; Moderated Mediation; Political Violence